The Princeton symposium on the American system of social insurance : its philosophy, impact, and future development - Brown, James Douglas; Bowen, William G..; Woodrow Wilson School of Public and International Affairs; Princeton University (New York: McGraw-Hill, 1968)
This volume contains the papers, together with a summary of the discussion, presented at a symposium on the American system of social insurance held at Princeton University on June 1 and 2, 1967, under the sponsorship of the Industrial Relations Section and the Woodrow Wilson School of Public and International Affairs. The chapters in this book deal both with specific programs of social insurance as well as with the impact and philosophy of the system as a whole. The first chapter gives an overview of the social insurance system with particular emphasis on the issue of federalism. The next chapter examines the role of social insurance in an overall national program for social welfare. Chapter 3 analyzes the critical aspects of financing the system. The focus then shifts to individual programs in the next chapter on old-age, survivors, and disability insurance. This is followed by a chapter on Medicare, and another on the uses of unemployment insurance. In chapter 7 the emphasis shifts again to impacts of the social insurance system on private benefit plans, and then to a comparison of America's philosophy of social insurance with that of European countries.
Held in honor of J. Douglas Brown.
"A project of the Industrial Relations Section and the Woodrow Wilson School of Public and International Affairs, Princeton University."
Includes bibliographical footnotes.
ne 11/05/2018
Loans
Keywords: Social Security; Social insurance; American system; America